Implementasi Metode Pembelajaran Pq4r untuk Meningkatkan Hasil Belajar Ekonomi Siswa Kelas X SMA Negeri 7 Halmahera Selatan - Rahmat Mamuasi; Fahri Samin (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the level of activity and student learning outcomes through the implementation of the PQ4R strategy (Preview, Question, Read, Reflect, Recite and Review) in the subject matter of financial services authority in class X IIS I SMA Negeri 7 Halmahera Selatan 2019 academic year. Type of research This is included in the classroom action research (CAR). The PQ4R strategy research procedure was carried out in 4 stages, namely planning, acting, observing, and reflecting. The types of research instruments used to collect data are observation sheets, questionnaires and learning achievement tests. The PQ4R strategy was assessed by 1 observer, the teacher as presenter and 35 students as subjects. The teachers and those involved in this study came from SMA Negeri 7 Halmahera Selatan. The data obtained were analyzed using quantitative to determine individual completeness and classical mastery. The results of this study indicate that the implementation of the PQ4R learning method can increase the activity and learning outcomes, based on the results of the analysis in cycle I and cycle II it is known that student activity and learning outcomes during the learning process always increase. Student activity in the first cycle of the first meeting obtained 50% of the second meeting 60%, the average activity was 81% in the good category. While the activity in cycle II increased at the first meeting to get 80%, the second meeting was 90% and the average percentage was 80.50% in the good category. Learning outcomes in the first cycle with an average value of 80%, 87% classical completeness.